Towards formulating a comprehensive social security scheme for Lesotho - Mosito, Kananelo E (Department of Public Law, 2024)
In most African countries, social development continues to raise grave concern as the majority of the population is afflicted by a litany of inexhaustible social risks. These social risks include: lack of social welfare services, social marginalisation, the HlV and AIDS pandemic, ill-health, poverty, unemployment, lack of education and training, lack of food and nutrition, low life expectancy, an increase in child and infant mortality and morbidity, and increase of women's death in child birth. This situation is aggravated by: The impact of globalisation on all social and economic policies which left the most vulnerable to be among the poorest of the poor. This situation has ...undermined social justice and equality and created marginalisation and exclusion of social groups, in particular the most vulnerable ones. These challenges need to be addressed by looking at the human dimension and the rights of people to have a decent and affordable life. An improvement in quality of life and livelihood depends on a social transformation which Governments should be ready to implement at the national level. The purpose of this chapter is to lay the foundation for the present thesis. The chapter begins by outlining the problem for the study. It thence presents the purpose of this study. It then continues to afford the rationale for the study. The chapter goes on to provide a theoretical foundation for the study.